The “piroplasmosis-like” syndrome in cattle on Réunion Island: Spatial and temporal distribution of cases and clinical impact of co-infections - William RJ Sercombe; Anaïs Etheves; Aurélia Garrigues; Bertrand Malivert; Xavier Plaëtevoët; Yannick Grimaud; Cécile Squarzoni; Sylvie Ahoussou; David A. Wilkinson (Preventive Veterinary Medicine, 2026)

A review of the index of biodiversity potential (IBP) as a tool for biodiversity evaluation in forest ecosystems - Laurent Larrieu; Pierre Gonin; Céline Emberger; Christian Ammer; Romain Angeleri; Teresa Baiges; Lorenzo Balducci; Antoine Brin; Rita Bütler; Jordi Camprodon; Teresa Cervera; Floriane Clement; et al. (European Journal of Forest Research, 2026)

Vibrio Community Structure Shapes the Diversity of Carbenicillin‐Hydrolysing Class A β‐Lactamase Circulating in European Coastal Environments - Berenice Reggiardo; Jamal Saad; Marie‐Agnès Travers; Yannick Labreuche; David Goudenège; Eve Toulza; Coralie Broquard; Karl B. Andree; Julia Mougin; Nicolas Argenta; Gaëlle Courtay; Juliette Pouzadoux; et al. (Environmental Microbiology, 2026)
Coastal environments are increasingly recognised as reservoirs of known antibiotic resistance genes (ARGs), but are less frequently identified as sources of novel ARGs. Here, we investigated class A β‐lactamases circulating in European coastal environments used for oyster farming. We examined their diversity, function, and the ecological factors associated with their geographic distribution and environmental dynamics. A high diversity of carbenicillinases was detected in the culturable microbiome of European oysters. The Harveyi and Splendidus clades were key Vibrio lineages structuring the geography of carbenicillinase diversity. The Harveyi clade was primarily associated with the circulation of known carbenicillinases in Mediterranean samples, whereas the Splendidus clade contributed previously uncharacterized carbenicillinase sequences across all Europe. A one‐year seasonal monitoring revealed that Vibrio alginolyticus drives the circulation of bla CARB‐42 in the Mediterranean Thau lagoon, with dynamics strongly associated with seawater temperature. bla CARB‐42 conferred intrinsic resistance to both carboxypenicillins and aminopenicillins in V. alginolyticus , which was found in most other species of the Harveyi clade with additional resistances to aztreonam, third‐generation cephalosporins and aminoglycosides. Since the Harveyi clade includes major human pathogens, these findings have direct implication for environmental and One Health surveillance, as rising seawater temperatures may increase coastal exposure to antibiotic‐resistant Harveyi clade Vibrio .

Trends and risk factors of antimicrobial resistance of Neisseria gonorrhoeae in Catalonia, Spain, 2022–2023 - Mercè Herrero; Sonia Broner; Naiana Pastrana-Batalla; Eduard Anfruns; Evelin López-Corbeto; Victoria González; Judit Serra-Pladevall; Nieves Larrosa; Jacobo Mendioroz; Pilar Ciruela; Yuliya Poliakova; Mateu Espasa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Decoding Temporomandibular Disorders: Identifying Stage-Specific and Functional Patterns in the Articular Disc - Pascal Eber; Ana M. P. Baggio; Yannick M. Sillmann; Philippe Korn; David A. Keith; Shruti Handa; Fernando P. S. Guastaldi (Stem Cell Reviews and Reports, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

Progress, challenges and future directions in marine organic-walled dinoflagellate cyst research: New insights from an international workshop - Iria García-Moreiras; Ana Amorim; Vera Pospelova; Karin Zonneveld; Donald M. Anderson; Girish Beedessee; Amy Dale; Barrie Dale; Ophélie David; Anne de Vernal; Eugenia Fatourou; Emilie Folie-Boivin; et al. (Marine Micropaleontology, 2025)

Towards a New Interpretative Framework for Air Quality and Climate Biomonitoring With Lichens: A Meta‐Analysis of Surveys Using the European Protocol - Hugo Counoy; Laure Turcati; Patrick Bogaert; Gregory Agnello; Annabelle Austruy; Franc Batič; Catherine Biache; Claire Boucheron; Lisa Brancaleoni; Cristina Branquinho; Miris Castello; Immacolata Catalano; et al. (Global Change Biology, 2025)
Air pollution and climate change remain critical environmental challenges, particularly in urban areas, where conventional monitoring networks are often too sparse to capture fine‐scale exposure gradients due to their high operational costs. Epiphytic lichen biomonitoring provides a valuable complementary approach, as these organisms are sensitive to both air pollutants and climate conditions. Despite the existence of a standardized European protocol, large‐scale implementation is hindered by the absence of a robust interpretative framework and incomplete knowledge of species‐specific responses to pollutants and climate variables. This study initiated the development of a standardized interpretative framework for European lichen biomonitoring data by identifying a core set of indicator species with clear responses to major air pollutants and climate variables. To achieve this, we compiled and harmonized raw lichen data from 58 studies that applied the European protocol and modeled the response of 43 lichen species to dominant air pollutants (NH 3 , NO x , and SO 2 ) and climate variables (mean air temperature, mean relative humidity, and temperature seasonality). While confirming established trends, our models allowed us to decouple species responses to reduced (NH 3 ) vs. oxidized (NO x ) nitrogen compounds, a distinction rarely achievable in local studies due to insufficient contrast in pollutant gradients. We also provided actionable recommendations to enhance comparability, such as prioritizing widespread, well‐studied tree species and standardizing lichen taxa groupings. Our study established a foundation for a harmonized European interpretative framework by identifying low‐bias, ecologically meaningful indicator species. Future efforts should focus on translating sensitivity classifications into actionable air quality indices and refining regional‐scale assessments.

Reverse chemical ecology to study the defense of the plant host Sextonia rubra and the chemical mediators of its endophyte Fusarium falciforme against phytopathogen Trametes versicolor - Marceau Levasseur; Alice Trac; Isabelle Clavereau; Flavien Zannini; Yannick Estevez; Nadine Amusant; Éric Gelhaye; Nicolas Pollet; Emeline Houël; David Touboul; Véronique Eparvier (Phytochemistry, 2025)

Environmental and climatic evolution of a river-proximal peatland in the Cuvette Centrale, Congo Basin - Johanna Menges; David Sebag; Judicael Lebamba; Chris Kiahtipes; Hans-Peter Wotzka; Johannes Preuß; Ferdinand Bokomba Bwamangele; Roger Kidebua Lutonadio; Melanie Guardiola; Thierry Adatte; Yannick Stroobandt; Steven Bouillon; et al. (Quaternary Science Reviews, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Sensitivity to climate and vegetation dynamics of a peatland record from central Cameroon during the African Humid Period - Valentine Schaaff; Vincent Grossi; Matthew Makou; Yannick Garcin; Pierre Deschamps; Bruno Hamelin; Christopher A. Kiahtipes; David Sebag; Benjamin Ngounou Ngatcha; Guillemette Ménot (Quaternary Science Reviews, 2025)

Evaluation of the Tuskegee University and USDA-FAS training workshop leveraging US biotechnology and biosafety for Côte d'Ivoire experts - Marceline Egnin; Curtis Jolly; Chia Valentine Gnaoré-Yapi; Colette Kouamé-Singo; Yannick Alain Troupah; Niamké L. Sébastien Ahonzo; Conrad Bonsi; Ellene Kebede; David Songstad; Suchet Loois; Karimbhai Maredia; Walter Hill (In Vitro Cellular & Developmental Biology - Plant, 2025)

Advances in environmental biotechnology and engineering - Hervé Macarie; Catherine Rébufa; Yveline Le Dréau; Carlos Escamilla-Alvarado; David Fernández-Domínguez; Yannick Combet-Blanc; Isabel Sastre-Conde (Environmental Science and Pollution Research, 2025)

Daily Sun‐induced chlorophyll fluorescence vs. irradiance curves reflect the photoadaptation of phytoplankton in surface waters - Yannick Huot; David Antoine; Vincenzo Vellucci (Limnology and Oceanography, 2025)
Phytoplankton chlorophyll Sun‐induced fluorescence is observable in the upwelling light field of the ocean. This allows its observation by radiometers in situ or on satellite sensors. Since it is influenced by both biomass and physiology it can potentially provide information about both. Since fluorescence yield is complementary to photosynthesis and heat in photosystem II, its observation throughout the day provides information on the response of phytoplankton to diel light cycles. Here we use a time series collected in the northwestern Mediterranean Sea (BOUSSOLE site) to extract photophysiological parameters of phytoplankton using the Sun‐induced fluorescence and as well as with an active chlorophyll fluorometer. The daily resolved patterns are consistent with photoacclimation and photoadaptation processes and reflect seasonal variations of the mixed‐layer average irradiance. We also show that fluorescence yields derived from satellite measurements (MODIS) at the same location are not correlated to these patterns, confirming the limited influence of photoacclimation and photoadaptation on the satellite‐derived chlorophyll fluorescence yield near solar noon.

Exploration of microRNAs in butter and their potential influence on human health - Christine Leroux; Yannick Faulconnier; Sebastien Bes; J. Bruce German; David A. Mills; Fabienne Le Provost; Sandrine Le Guillou (International Dairy Journal, 2025)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Bio-optical variability of particulate matter in the Southern Ocean - Juan Li; David Antoine; Yannick Huot (Frontiers in Marine Science, 2024)
The composition and size distribution of particles in the ocean control their optical (scattering and absorption) properties, as well as a range of biogeochemical and ecological processes. Therefore, they provide important information about the pelagic ocean ecosystem’s structure and functioning, which can be used to assess primary production, particle sinking, and carbon sequestration. Due to its harsh environment and remoteness, the particulate bio-optical properties of the Southern Ocean (SO) remain poorly observed and understood. Here, we combined field measurements from hydrographic casts from two research voyages and from autonomous profiling floats (BGC-Argo) to examine particulate bio-optical properties and relationships among several ecologically and optically important variables, namely the phytoplankton chlorophyll a concentration (Chl), the particulate absorption coefficient ( a p ), the particulate backscattering coefficient ( b bp ), and the particulate organic carbon (POC) concentration. In the clearest waters of the SO (Chl < 0.2 mg m −3 ), we found a significant contribution to absorption by non-algal particles (NAP) at 442 nm, which was up to 10 times greater than the absorption by phytoplankton. This makes the particulate bio-optical properties there remarkably different from typical oceanic case 1 water. A matchup analysis confirms the impact of this larger NAP absorption on the retrieval of Chl from satellite ocean colour observations. For waters with Chl > 0.2 mg m −3 , no significant differences are observed between the SO and temperate waters. Our findings also demonstrate consistency in predicting phytoplankton carbon from either Chl or b bp , suggesting that both methods are applicable in the SO.

GNSS Solar Astronomy in real-time during more than one solar cycle - Manuel Hernández-Pajares; Alberto García-Rigo; Enric Monte-Moreno; Qi Liu; David Roma-Dollase; Heng Yang; Yannick Béniguel; David Moreno-Borràs; Octavi Fors; Haixia Lyu; Raul Orus-Perez; Javier Ventura-Traveset (Advances in Space Research, 2024)

Constraints on hopanes and brGDGTs as pH proxies in peat - Valentine Schaaff; Vincent Grossi; Matthew Makou; Yannick Garcin; Pierre Deschamps; David Sebag; Benjamin Ngounou Ngatcha; Guillemette Ménot (Geochimica et Cosmochimica Acta, 2024)

The challenge of assessing the effects of drifting fish aggregating devices on the behaviour and biology of tropical tuna - Amaël Dupaix; Frédéric Ménard; John D. Filmalter; Yannick Baidai; Nathalie Bodin; Manuela Capello; Emmanuel Chassot; Hervé Demarcq; Jean‐Louis Deneubourg; Alain Fonteneau; Fabien Forget; Francesca Forrestal; et al. (Fish and Fisheries, 2024)
Fishers have intensively used drifting fish aggregating devices (DFADs) over the last three decades to facilitate their catch of tropical tunas. DFADs increase purse‐seine efficiency, potentially increasing tuna fishing mortality. They could also have impacts on tuna natural mortality and reproductive potential, and assessing the consequences of their presence at sea on tuna populations is a challenge. The use of DFADs results in a major increase in the number of floating objects, which are spatially heterogeneous at sea. To date, no converging scientific results exist regarding the effects of DFADs on the large‐scale movements and behaviour of tuna, mainly due to the difficulty of disentangling the respective roles of DFADs and environmental factors. Some biological indices show that tuna condition is lower when associated to a floating object than in a free‐swimming school. However, it is not clear whether this is the cause or the consequence of the association nor if it has long‐term effects on individuals' fitness. Further scientific progress requires (i) the collection of time series of indicators to monitor habitat change, individual behaviour, individual fitness, and population dynamics and (ii) experimental studies to identify the underlying behavioural and biological processes involved in associative behaviour. The extent of the modification of the surface habitat by the massive deployment of DFADs and the current uncertainty of the possible long‐term consequences on the individual fitness and dynamics of tuna populations argue for the need for increased awareness of this issue by Regional Fisheries Management Organisations regulating tuna fishing.

Species identification of fish shoals using coupled split-beam and multibeam echosounders and two scuba-diving observational methods - Viviane David; Anne Mouget; Pierre Thiriet; Corentin Minart; Yannick Perrot; Loïc Le Goff; Olivier Bianchimani; Solène Basthard-Bogain; Tristan Estaque; Justine Richaume; Jean-François Sys; Adrien Cheminée; et al. (Journal of Marine Systems, 2024)

Measurement of fine particle concentrations and estimation of air quality index (AQI) over northeast Douala, Cameroon - Cyrille Adiang Mezoue; Yannick Cedric Ngangmo; Arti Choudhary; David Monkam (Environmental Monitoring and Assessment, 2023)

Genomic evidence for three distinct species in the Erebia manto complex in Central Europe (Lepidoptera, Nymphalidae) - Amanda Jospin; Yannick Chittaro; Daniel Bolt; David Demergès; Kevin Gurcel; Jürgen Hensle; Andreas Sanchez; Christophe Praz; Kay Lucek (Conservation Genetics, 2023)
A problem to implement conservation strategies is that in many cases recognized taxa are in fact complexes of several cryptic species. Failure to properly delineate species may lead to misplaced priorities or to inadequate conservation measures. One such species complex is the yellow-spotted ringlet Erebia manto , which comprises several phenotypically distinct lineages, whose degree of genomic isolation has so far not been assessed. Some of these lineages are geographically restricted and thus possibly represent distinct units with conservation priorities. Using several thousand nuclear genomic markers, we evaluated to which degree the bubastis lineage from the Alps and the vogesiaca lineage from the Vosges, are genetically isolated from the widespread manto lineage. Our results suggest that both lineages are genetically as strongly differentiated from manto as other taxonomically well separated sibling species in this genus from each other, supporting a delineation of bubastis and vogesiaca as independent species. Given the restricted and isolated range of vogesiaca as well as the disjunct distribution of bubastis, our findings have significant implication for future conservation efforts on these formerly cryptic species and highlight the need to investigate the genomic identity within species complexes.

Enhanced Drug Delivery for Cardiac Microvascular Obstruction with an Occlusion-Infusion-Catheter - Yannick Rösch; David Eggenberger; Yves Kuster; Lino Widmer; Sabrina Frey; Rob Schwartz; Cornelia Nef; Jens Ulmer; Dominik Obrist (Annals of Biomedical Engineering, 2023)
Microvascular Obstruction (MVO) is a common consequence of acute myocardial infarction. MVO is underdiagnosed and treatment is often nonspecific and ineffective. A multi-scale in-vitro benchtop model was established to investigate drug perfusion in MVO affected microcirculation. The central element of the benchtop model was a fluidic microchip containing channels with diameters between $$555$$ 555 and 50 μ m representing $$2%$$ 2 % of the microvascular tree fed by the left anterior descending artery (LAD). The outlets of the chip could be closed to mimic MVO. Two methods for intracoronary infusion of pharmacologic agents (simulated by dye) to regions with MVO were investigated using an occlusion-infusion catheter. The first case was a simple, bolus-like infusion into the LAD, whereas the second case consisted of infusion with concomitant proximal occlusion of the LAD phantom with a balloon. Results show that local dye concentration maxima in the chip with MVO were 2.2–3.2 times higher for the case with proximal balloon occlusion than for the conventional infusion method. The cumulated dose could be raised by a factor 4.6–5.2. These results suggest that drug infusion by catheter is more effective if the blood supply to the treated vascular bed is temporarily blocked by a balloon catheter.

Modeling the decomposition signal and correcting bulk organic data from a peat deposit, a case study at low latitudes (Cameroon) - Valentine Schaaff; David Sebag; Matthew Makou; Vincent Grossi; Ingrid Antheaume; Bruno Hamelin; Yannick Garcin; Benjamin Ngounou Ngatcha; Pierre Deschamps; Guillemette Ménot (Organic Geochemistry, 2023)

Functional and targeted proteomics characterization of a human primary endothelial cell model of the blood-brain barrier (BBB) for drug permeability studies - David Gomez-Zepeda; Nicolas Perrière; Fabienne Glacial; Meryam Taghi; Cérina Chhuon; Jean-Michel Scherrmann; Philippe Sergent; Amélie Moreau; Claire Denizot; Yannick Parmentier; Salvatore Cisternino; Xavier Decleves; et al. (Toxicology and Applied Pharmacology, 2023)

Geospatial analysis reveals a hotspot of fecal bacteria in Canadian prairie lakes linked to agricultural non-point sources - Anaïs Oliva; Vera E. Onana; Rebecca E. Garner; Susanne A. Kraemer; Maxime Fradette; David A. Walsh; Yannick Huot (Water Research, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Hippocampal Cannabinoid 1 Receptors Are Modulated Following Cocaine Self-administration in Male Rats - David De Sa Nogueira; Romain Bourdy; Rafael Alcala-Vida; Dominique Filliol; Virginie Andry; Yannick Goumon; Jean Zwiller; Pascal Romieu; Karine Merienne; Mary C. Olmstead; Katia Befort (Molecular Neurobiology, 2022)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Mineralogy and geochemistry study of the Nyong River sediments, SW Cameroon: Implications for provenance, weathering, and tectonic setting - Yannick Steve Ngagoum Kontchipe; Francis Temgo Sopie; Gabriel Ngueutchoua; Aristide Nadine Sonfack; David Guimolaire Nkouathio; Robinson Tchatchueng; Gatien Romuald Kenfack Nguemo; Théophile Njanko (Arabian Journal of Geosciences, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Microbial life under ice: Metagenome diversity and in situ activity of Verrucomicrobia in seasonally ice‐covered Lakes - Patricia Tran; Arthi Ramachandran; Ola Khawasik; Beatrix E. Beisner; Milla Rautio; Yannick Huot; David A. Walsh (Environmental Microbiology, 2018)
Summary Northern lakes are ice‐covered for a large part of the year, yet our understanding of microbial diversity and activity during winter lags behind that of the ice‐free period. In this study, we investigated under‐ice diversity and metabolism of Verrucomicrobia in seasonally ice‐covered lakes in temperate and boreal regions of Quebec, Canada using 16S rRNA sequencing, metagenomics and metatranscriptomics. Verrucomicrobia, particularly the V1, V3 and V4 subdivisions, were abundant during ice‐covered periods. A diversity of Verrucomicrobia genomes were reconstructed from Quebec lake metagenomes. Several genomes were associated with the ice‐covered period and were represented in winter metatranscriptomes, supporting the notion that Verrucomicrobia are metabolically active under ice. Verrucomicrobia transcriptome analysis revealed a range of metabolisms potentially occurring under ice, including carbohydrate degradation, glycolate utilization, scavenging of chlorophyll degradation products, and urea use. Genes for aerobic sulfur and hydrogen oxidation were expressed, suggesting chemolithotrophy may be an adaptation to conditions where labile carbon may be limited. The expression of genes for flagella biosynthesis and chemotaxis was detected, suggesting Verrucomicrobia may be actively sensing and responding to winter nutrient pulses, such as phytoplankton blooms. These results increase our understanding on the diversity and metabolic processes occurring under ice in northern lakes ecosystems.© 2018 Society for Applied Microbiology and John Wiley & Sons Ltd

The role of evaporites in the formation of gems during metamorphism of carbonate platforms: a review - Gaston Giuliani; Jean Dubessy; Daniel Ohnenstetter; David Banks; Yannick Branquet; Julien Feneyrol; Anthony E. Fallick; Jean-Emmanuel Martelat (Mineralium Deposita, 2018)

A single regulatory gene is sufficient to alter V ibrio aestuarianus pathogenicity in oysters - David Goudenège; Marie Agnès Travers; Astrid Lemire; Bruno Petton; Philippe Haffner; Yannick Labreuche; Delphine Tourbiez; Sophie Mangenot; Alexandra Calteau; Didier Mazel; Jean Louis Nicolas; Annick Jacq; et al. (Environmental Microbiology, 2015)
Summary Oyster diseases caused by pathogenic vibrios pose a major challenge to the sustainability of oyster farming. In F rance, since 2012 a disease affecting specifically adult oysters has been associated with the presence of V ibrio aestuarianus. Here, by combining genome comparison, phylogenetic analyses and high‐throughput infections of strains isolated before or during the recent outbreaks, we show that virulent strains cluster into two V . aestuarianus lineages independently of the sampling dates. The bacterial lethal dose was not different between strains isolated before or after 2012. Hence, the emergence of a new highly virulent clonal strain is unlikely. Each lineage comprises nearly identical strains, the majority of them being virulent, suggesting that within these phylogenetically coherent virulent lineages a few strains have lost their pathogenicity. Comparative genomics allowed the identification of a single frameshift in a non‐virulent strain. This mutation affects the varS gene that codes for a signal transduction histidine‐protein kinase. Genetic analyses confirmed that varS is necessary for infection of oysters and for a secreted metalloprotease expression. For the first time in a V ibrio species, we show here that VarS is a key factor of pathogenicity.

Flagella interact with ionic plant lipids to mediate adherence of pathogenic Escherichia coli to fresh produce plants - Yannick Rossez; Ashleigh Holmes; Eliza B. Wolfson; David L. Gally; Arvind Mahajan; Henriette L. Pedersen; William G.T. Willats; Ian K. Toth; Nicola J. Holden (Environmental Microbiology, 2014)
Summary Bacterial attachment to plant and animal surfaces is generally thought to constitute the initial step in colonization, requiring adherence factors such as flagella and fimbriae. We describe the molecular mechanism underpinning flagella‐mediated adherence to plant tissue for the foodborne pathogen, enterohaemorrhagic E scherichia coli . E scherichia coli H 7 flagella interacted with a sulphated carbohydrate (carrageenan) on a glycan array, which occurred in a dose‐dependent manner. Adherence of E . coli O 157 : H ‐expressing flagella of serotype H 7, H 6 or H 48 to plants associated with outbreaks from fresh produce and to A rabidopsis thaliana , was dependent on flagella interactions with phospholipids and sulpholipids in plasma membranes. Adherence of purified H 7 and H 48 flagella to carrageenan was reduced at higher concentrations of KH 2 PO 4 or KCl , showing an ionic basis to the interactions. Purified H 7 flagella were observed to physically interact with plasma membranes in spinach plants and in A . thaliana . The results show a specific interaction between E . coli H 7, H 6 and H 48 flagella and ionic lipids in plant plasma membranes. The work extends our understanding of the molecular mechanisms underpinning E . coli flagella targeting of plant hosts and suggests a generic mechanism of recognition common in eukaryotic hosts belonging to different biological kingdoms.

Cyclooxygenase-2 positively regulates Akt signalling and enhances survival of erythroleukemia cells exposed to anticancer agents - Julian Bertrand; Bertrand Liagre; Lamia Ghezali; Jean-Louis Beneytout; David Yannick Leger (Apoptosis, 2013)

Combined linkage and association mapping of flowering time in Sunflower (Helianthus annuus L.) - Elena Cadic; Marie Coque; Felicity Vear; Bruno Grezes-Besset; Jerôme Pauquet; Joël Piquemal; Yannick Lippi; Philippe Blanchard; Michel Romestant; Nicolas Pouilly; David Rengel; Jerôme Gouzy; et al. (Theoretical and Applied Genetics, 2013)

New Cultural Approaches for Microaerophilic Hyperthermophiles - Rafael Uzarraga; Richard Auria; Sylvain Davidson; David Navarro; Yannick Combet-Blanc (Current Microbiology, 2011)

Diel cycles of the particulate beam attenuation coefficient under varying trophic conditions in the northwestern Mediterranean Sea: Observations and modeling - Pierre Gernez; David Antoine; Yannick Huot (Limnology and Oceanography, 2011)
The changes in shape, amplitude, and timing in the diel variability of the particulate beam attenuation coefficient ( c p ) were investigated at 4 and 9 m during two seasonal cycles at an oceanic site in the northwestern Mediterranean Sea under contrasting physical and trophic situations. We observed a diel cycle in c p during the winter mixing of the water column, the development of the spring phytoplankton bloom, its collapse, and during the summer oligotrophy. The relative amplitude of the c p diel cycle was about 10–20% during winter mixing and summer oligotrophy and at least twice as large during the spring bloom. Diel c p minima generally occurred around sunrise and maxima a few hours before sunset. The specific particle rate of variation ( r ) was consistent over the diel cycle, with positive and negative values during daytime and nighttime, respectively. A striking feature of the r diel cycle was a morning maximum, i.e., before solar noon, which was successfully reproduced by a new model of particle assemblage growth rate based on three parameters: maximum growth rate, growth efficiency, and saturation irradiance. Each model parameter undergoes a diel cycle and shows a seasonal variation. A c p ‐based estimation of the particle net community production is computed from the measurements and model outputs. Results compare favorably with modeled primary production on the basis of continuous measurements of surface chlorophyll using fluorescence.

Solar and anthropogenic imprints on Lake Masoko (southern Tanzania) during the last 500 years - Yannick Garcin; David Williamson; Laurent Bergonzini; Olivier Radakovitch; Annie Vincens; Guillaume Buchet; Joël Guiot; Simon Brewer; Pierre-Etienne Mathé; Amos Majule (Journal of Paleolimnology, 2007)